Water volume reduction increases eutrophication risk in tropical semi-arid reservoirs - Rocha Junior,Carlos Alberto Nascimento da (2018)
Abstract Aim Global patterns of temperature and precipitation have significantly changed over the last century and nearly all predictions point to even greater changes by the end of 2100. Long periods of drought in semi-arid regions generally reduce reservoirs and lakes water level, increasing the nutrients concentrations in the water. Our principal hypothesis is that water volume reduction, driven by prolonged droughts, will increase reservoirs susceptibility to eutrophication and accordingly an increase in trophic state. To test this hypothesis, we used a comparative analysis of ecosystems in a space-for-time substitution approach, in a Brazilian semi-arid region, to predict the consequences of reservoirs water volume reduction on key limnological variables. Methods We sampled 16 reservoirs located in two sub-basins with contrasting rainfall regimes, inserted on Piranhas-Açu watershed. The Seridó River basin (SB) is dry and the Piancó River basin (SB) is humid, with annual mean precipitation of 500 and 700 mm, respectively. Linear regressions analyzes were performed to assess whether the percentage of maximum volume stored (%MVS) is a good predictor for total phosphorus (TP), total nitrogen (TN) and chlorophyll-a (CHLA). In addition, a two factorial analysis of variance (two-way ANOVA) was performed to test for period (dry, very dry and extremely dry), basin (SB and PB) and their interactions effects on TP, TN, CHLA, conductivity, turbidity, and Secchi depth. Results The results showed a reduction in the reservoirs %MVS both for PB and SB regions. At the extremely dry period, all reservoirs were classified as eutrophic, but TP concentrations reached much higher values in SB than in PB. The linear regressions analyses showed that the TP and TN were negatively related to %MVS during all periods sampled. The two-way ANOVA showed that there were significant basin and period effects on TP, TN, Secchi depth and turbidity, whereas for CHLA and conductivity only basin effects were observed. In addition, we found significant interaction effects between period and basin on TP, TN and turbidity. Conclusions We conclude that the contrasting levels of rainfall observed between the two basins affect the water quality and trophic state of the reservoirs and these effects are magnified by water volume reduction. Therefore, our findings might help to predict the consequences of rainfall reductions on freshwater ecosystems of Brazilian drylands.